2008
DOI: 10.1103/physrevlett.100.215001
|View full text |Cite
|
Sign up to set email alerts
|

Tempest Simulations of Collisionless Damping of the Geodesic-Acoustic Mode in Edge-Plasma Pedestals

Abstract: The fully nonlinear (full-f) four-dimensional TEMPEST gyrokinetic continuum code correctly produces the frequency and collisionless damping of geodesic-acoustic modes (GAMs) and zonal flow, with fully nonlinear Boltzmann electrons for the inverse aspect ratio scan and the tokamak safety factor q scan in homogeneous plasmas. TEMPEST simulations show that the GAMs exist in the edge pedestal for steep density and temperature gradients in the form of outgoing waves. The enhanced GAM damping may explain experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
99
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 11 publications
(21 reference statements)
10
99
0
Order By: Relevance
“…They numerically evaluated the influence of toroidal Mach number on the Landau damping rate by considering from 2nd to 5th FOW resonance effect, respectively. Similar to the case without toroidal rotation [5,6,10], they found that the damping rate was significantly enhanced by 3rd resonance and the damping rate with 3rd resonance and the one with 4th * Electronic address: hjren@ustc.edu.cn or 5th resonance are almost the same with each other. In this Letter, theoretical investigation on the collisionless damping of GAM in a toroidally rotating tokamak plasma is performed.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…They numerically evaluated the influence of toroidal Mach number on the Landau damping rate by considering from 2nd to 5th FOW resonance effect, respectively. Similar to the case without toroidal rotation [5,6,10], they found that the damping rate was significantly enhanced by 3rd resonance and the damping rate with 3rd resonance and the one with 4th * Electronic address: hjren@ustc.edu.cn or 5th resonance are almost the same with each other. In this Letter, theoretical investigation on the collisionless damping of GAM in a toroidally rotating tokamak plasma is performed.…”
supporting
confidence: 66%
“…When only the 2-nd resonance is taken into account, a recent NEMORB simulation [8] performed a good agreement with the analytical result to the 2-nd FOW effects for about q < 3.5 [2]. It was shown that for q > 3.5, the discrepancy between the theoretical result with 2nd harmonics and the TEMPEST simulation data becomes remarkable [6]. That means higher-order resonance should be considered.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Radial propagation of geodesic acoustic modes (GAMs) [1], and GAM eigenmodes have been discussed in recent literature [2][3][4]. The existence and properties of global GAM eigenmodes, which are influenced by the GAM group velocity, might be relevant for the efficiency of GAM excitation [4,5].…”
Section: Introductionmentioning
confidence: 99%